Study of tissue damage in the respiratory system of patients with COVID-19 in Al-Muthanna Governorate - Alhamadani, Yousif; Hassan, Rima (Journal of Biomedicine and Biochemistry, 2022)
The object of study was conducted on 30 patients from three different geographical areas of Al-Muthanna Governorate, Samawah city, Al-Rumaitha district, and Al-Khader. The study was conducted on 30 patients, 18 females and 12 males. Ages ranges were between 20 – 75 years old. The aim of study was determination tissue damage levels in the  respiratory system in patients with COVID-19. The study showed that females are more susceptible to get COVID-19 than males Percentage of females was 60%. the percentage of tissue damage in the tissues of the respiratory system wide range between 2 - 80% Percentage of damage at the site of the lungs and main bronchi which is the most, was 55%. As for the ages of the patients, the study showed that the ages older than 60 years old 43.3% from total patients they are the ones most susceptible to infection. Relative to the rate of tissue damage in the respiratory system for patients older than 60 years old was 64.7%, it is the highest percentage of tissue damage in relation to other ages.